Pengaruh Gaya Kepemimpinan, Disiplin Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan - Rubi Raya Rizqika; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
The study was conducted to see and collect data on how leadership style, work discipline, and job satisfaction affect employee performance. The research I conducted used quantitative methods and descriptive analysis. For this study, data were collected online through a randomized method through a likert scale questionnaire 1-5 to 190 respondents who met the following criteria: they are over 18 years old and have worked or participated in an organization, team, or company. For data analysis, the SmartPLS application is used to perform inner measurements, reliability values, discriminant validity, Cronbach's Alpha, and exterior measurements. The outer measurements also use T-test calculations, determinacy coefficient, f-square, and VIF. The main purpose of this study is to prove that leadership style contributes positively to employee performance, work discipline has a positive influence on employee performance, and job satisfaction has a positive impact on employee performance.